2015
DOI: 10.1167/iovs.15-16560
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral Clinically Unaffected Eyes of Patients With Unilateral Infectious Keratitis Demonstrate a Sympathetic Immune Response

Abstract: We demonstrate a subclinical involvement in the contralateral clinically unaffected eyes in patients with unilateral acute MK. In vivo confocal microscopy reveals not only a diminishment of the subbasal corneal nerves and sensation, but also an increase in dendritiform cell density in the contralateral unaffected eyes of MK patients. These findings show bilateral immune alterations in a clinically unilateral disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 40 publications
2
48
0
1
Order By: Relevance
“…28,29 However, no significant difference was noted between our two groups after adjusting for clinical parameters including DED severity. Steger and associates 25 also have observed a significantly lower number of subbasal nerves per frame in the GVHD group than in a control group without GVHD.…”
Section: Discussionmentioning
confidence: 64%
“…28,29 However, no significant difference was noted between our two groups after adjusting for clinical parameters including DED severity. Steger and associates 25 also have observed a significantly lower number of subbasal nerves per frame in the GVHD group than in a control group without GVHD.…”
Section: Discussionmentioning
confidence: 64%
“…Although the molecular basis of corneal sensitivity remains unclear, previous reports have described the bilateral responses in the patients with unilateral diseases or peripheral unilateral nerve lesions, including the infectious keratitis, which may be related to the sympathetic reaction caused by the central nervous system. 19,[35][36][37] Considering that intravitreal-injected bevacizumab could be detected in the cornea, 38 multiple intravitreal injections of bevacizumab may cause impairment of corneal innervations and epithelial functions, which needs to be evaluated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…202 More recent prospective studies demonstrated that the decrease in subbasal corneal nerve density is associated with increased density and morphological changes of central epithelial dendritic cells in patients with infectious keratitis, including bacterial, fungal and Acanthamoeba keratitis, suggesting a potential direct interaction between the immune and nervous system in the cornea (Figure 7). 88,203 Kobayashi et al studied patients with cytomegalovirus corneal endotheliitis by IVCM and also found reduced subbasal nerves. 204 Recently, our group showed that patients with infectious keratitis who sustain profound loss of corneal nerves during the acute phase of infection experienced corneal nerve regeneration of subbasal nerves during the first 6 months after the resolution of infection.…”
Section: Correlation Of Corneal Nerve Alterations To Corneal Sensmentioning
confidence: 99%